2006
DOI: 10.1002/jcp.20847
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of FGF‐21 activity—synergy and cross‐talk with PPARγ signaling

Abstract: Fibroblast growth factor (FGF)-21 is a novel regulator of insulin-independent glucose transport in 3T3-L1 adipocytes and has glucose and triglyceride lowering effects in rodent models of diabetes. The precise mechanisms whereby FGF-21 regulates metabolism remain to be determined. Here we describe the early signaling events triggered by FGF-21 treatment of 3T3-L1 adipocytes and reveal a functional interplay between FGF-21 and peroxisome proliferator-activated receptor gamma (PPARg) pathways that leads to a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
130
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(144 citation statements)
references
References 29 publications
12
130
0
Order By: Relevance
“…Addition of recombinant FGF21 to adipocytes was found to stimulate insulin-independent glucose uptake by enhancing the expression of GLUT1 (7). A recent study has demonstrated a profound synergy between FGF21 and the antidiabetic agent rosiglitazone (a peroxisome proliferator-activated receptor ␥ [PPAR␥] agonist) in stimulating glucose uptake (14). The metabolic effects of FGF21 in adipocytes were mediated by ␤-Klotho, a single-pass transmembrane protein whose expression is induced during adipogenesis (15).…”
mentioning
confidence: 99%
“…Addition of recombinant FGF21 to adipocytes was found to stimulate insulin-independent glucose uptake by enhancing the expression of GLUT1 (7). A recent study has demonstrated a profound synergy between FGF21 and the antidiabetic agent rosiglitazone (a peroxisome proliferator-activated receptor ␥ [PPAR␥] agonist) in stimulating glucose uptake (14). The metabolic effects of FGF21 in adipocytes were mediated by ␤-Klotho, a single-pass transmembrane protein whose expression is induced during adipogenesis (15).…”
mentioning
confidence: 99%
“…Ligand activation of PPAR␥ acted in the opposite direction, inducing the transcription of Klb and its eRNAs. KLB was also found to be up-regulated in EWAT of mice treated with PPAR␥ ligands (58,59). Moreover, knockdown of PPAR␥ led to a decrease in KLB mRNA level in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 89%
“…However, this finding may not necessarily mean that the impact of FGF21 on glucose metabolism is insignificant. The effect of FGF21 on glucose uptake becomes evident several hours after the stimulation and lasts for 24 h or longer (7) even though FGF21-induced Akt phosphorylation diminishes within 30 min in 3T3-L1 adipocytes (17). In contrast, insulin-induced glucose uptake becomes evident within minutes after stimulation in these cells and attenuates within hours.…”
Section: Fgf21 Activity Depends On ␤Klotho Expression In Adipocytesmentioning
confidence: 99%